Hubungan Karakteristik Ibu Dan Pelaksanaan Inisiasi Menyusu Dini (IMD) Dengan Pemberian Asi Eksklusif Di Puskesmas Pegajahan KEC.Pegajahan KAB Serdang Bedagai Tahun 2023 - Lyly Irayani; Isyos Sari Sembiring; Emma Dosriamaya Noni Br. Simanjuntak; Fitriani Fitriani; Sulastri Sulastri (Jurnal Medika Husada, 2023)
Background The Indonesian government pays quite high attention, because of the importance of exclusive breastfeeding for the growth and development of babies. In 2012, Government Regulation (PP) no. 33 regarding exclusive breastfeeding. The PP states that exclusive breastfeeding is breast milk given to babies from birth for six months without adding and/or replacing other foods or drinks. It is also stated that every mother who gives birth must provide exclusive breast milk to the baby she gives birth to, unless there are justified obstacles. The aim is to guarantee the fulfillment of babies' rights to receive exclusive breast milk from birth until the age of six months. In order for the exclusive breastfeeding program to be successful, it requires support from all elements, including government, private sector and society. Objective To determine the relationship between maternal characteristics and the implementation of IMD with exclusive breastfeeding at the Pegajahan Community Health Center, Pegajahan District, Serdang Bedagai District in 2023. Method chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. Results: There is no significant relationship between age, education, profession and mother's parity and there is a significant relationship between the implementation of IMD and exclusive breastfeeding at the Pegajahan Community Health Center, Pegajahan District, Serdang Bedagai District.